Vessel‐specific quantification of blood oxygenation with T2‐relaxation‐under‐phase‐contrast MRI. Issue 3 (8th April 2013) - Krishnamurthy, Lisa C.; Liu, Peiying; Ge, Yulin; Lu, Hanzhang
<x xml:space="preserve">Abstract</x> Purpose Measurement of venous oxygenation (Yv) is a critical step toward quantitative assessment of brain oxygen metabolism, a key index in many brain disorders. The present study aims to develop a noninvasive, rapid, and reproducible method to measure Yv in a vessel‐specific manner. Theory The method, T2‐Relaxation‐Under‐Phase‐Contrast MRI, utilizes complex subtraction of phase‐contrast to isolate pure blood signal, applies nonslice‐selective T2‐preparation to measure T2, and converts T2 to oxygenation using a calibration plot. Methods Following feasibility demonstration, several technical aspects were examined, including validation with an established global Yv technique, test–retest reproducibility, sensitivity to detect oxygenation changes due to hypoxia and caffeine challenges, applicability of echo‐planar‐imaging (EPI) acquisition to shorten scan duration, and ability to study veins with a caliber of 1–2 mm. Results T 2‐Relaxation‐Under‐Phase‐Contrast was able to simultaneously measure Yv in all major veins in the brain, including sagittal sinus, straight sinus, great vein, and internal cerebral vein. T2‐Relaxation‐Under‐Phase‐Contrast results showed an excellent agreement with the reference technique, high sensitivity to oxygenation changes, and test–retest variability of 3.5 ± 1.0%. The use of segmented‐EPI was able to reduce the scan duration to 1.5 minutes. It was also feasible to study pial veins and deep veins. Conclusion T 2‐Relaxation‐Under‐Phase‐Contrast MRI is a promising technique for vessel‐specific oxygenation measurement. Magn Reson Med 71:978–989, 2014. © 2013 Wiley Periodicals, Inc.